68Ga PSMA PET-CT: New Hope in Prostate Cancer Imaging and Therapy - Dey, Shankar Kumar (Bangladesh Journal of Nuclear Medicine, 2019)
Prostate cancer is the second most common cancer in men. Its diagnosis and management are still challenging as both PSA levels and imaging have had their limitations. Prostate specific membrane antigen (PSMA) is aprostate specific cell surface protein and has been emerging as a novel target for PET imaging of prostate cancer. 68Ga PSMA PET-CT imaging have been shown as a better imaging technology in primary prostate cancer and at the same time detecting lymph node and bone metastases even in low PSA levels. Moreover, its counterpart 177 Lu PSMA has a great prospectto be used for the treatment of castration resistantprostate cancer. Bangladesh J. Nuclear Med. 22(1): 53-57, Jan 2019